Effect of antimicrobial usage on enteric bacterial populations with focus on virulence and resistance profiles of Escherichia coli in growing pigs - Fasina, Folorunso Oludayo (University of Pretoria, 2018)
Dissertation (MSc)--University of Pretoria, 2018.